Antioxidant Phytoconstituents From Onosma bracteata Wall. (Boraginaceae) Ameliorate the CCl4 Induced Hepatic Damage: In Vivo Study in Male Wistar Rats - Kumar, Ajay; Kaur, Varinder; Pandit, Kritika; Tuli, Hardeep Singh; Sak, Katrin; Jain, Subheet Kumar; Kaur, Satwinderjeet (Frontiers in Pharmacology, 2020)
Onosma bracteatum Wall. (Boraginaceae) is a highly valuable medicinal herb that is used for the treatment of fever, bronchitis, asthma, rheumatism, stomach irritation and other inflammatory disorders. The present study aims to explore the hepatoprotective potential of ethanolic extract (Obeth) from O. bracteatum aerial parts against carbon tetrachloride (CCl4) which causes hepatic damage in the male Wistar rats. Obeth showed effective radical quenching activity with an EC50 of 115.14 and 199.33 µg/ml in superoxide radical scavenging and lipid peroxidation analyses respectively along with plasmid DNA protective potential in plasmid nicking assay. The Obeth modulated mutagenicity of 2 Aminofluorine (2AF) in the pre-incubation mode of investigation (EC50 10.48 µg/0.1 ml/plate) in TA100 strain of Salmonella typhimurium. In in vivo studies, pretreatment of Obeth (50, 100 and 200 mg/kg) had the potential to normalize the biochemical markers aggravated by CCl4 (1ml/kg b.wt.) including liver antioxidative enzymes. Histopathological analysis also revealed the restoration of CCl4-induced liver histopathological alterations. Immunohistochemical studies showed that the treatment of Obeth downregulated the expression levels of p53 and cyclin D in hepatocytes. and downregulation in the Western blotting analysis revealed the downregulation of p-NF-kB, COX-2 and p53. HPLC data analysis showed the supremacy of major compounds namely, catechin, kaempferol, epicatechin and Onosmin A in Obeth. The present investigation establishes the hepatoprotective and chemopreventive potential of O. bracteatum against CCl4-induced hepatotoxicity via antioxidant defense system and modulation of the expression of proteins associated with the process of carcinogenesis in hepatic cells.